Games of strategy - Dixit, Avinash K.; Skeath, Susan (New York : W. W. Norton, 1999)
Introduction and general principles. Concepts and techniques. Some broad classes of games and strategies. Applications to specific strategic situations.
Includes bibliographical references and index.
Keywords: Policy sciences; Decision making; Game theory; Policy sciences; Game theory; Decision making